PEMETAAN INTELLECTUAL CAPITAL INDUSTRI KREATIF DI JAWA TIMUR - Gendut Sukarno; Wulan Retno Wigati; Sulastri Irbayuni; Mas Anienda Tien Fitriyah (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
One of approach used in knowledge asset (knowledge property/asset) assessment and measurement was Intellectual Capital that comprised of 3 main elements of Human Capital, Structural Capital, and Relational Capital. Creative industry is industry with uniqueness and put more emphasize on creativity, innovation and individual talent utilization require maximum management. This research intended to find model, on how correct intellectual capital component would be, and find actual description of Human Capital, Structural Capital as well as Relational Capital principles for creative industry in East Java. Samples in this research were leader/management/owner of 5 creative industry sub-sectors in 9 cities of East Java (Surabaya, Pasuruan, Probolinggo, Mojokerto, Batu, Malang, Kediri, Blitar, and Madiun) with 45 people respondents as samples. Analysis technique utilized in this research was Spider Plot Diagram. Survey and discussion result showed that Intellectual Capital Mapping on 5 (five) creative industry sub-sectors in East Java demonstrated that Relational Capital was more dominant followed by Human Capital, and Structural Capital as the least dominant.